CEP131 indicates poor prognosis and promotes cell proliferation and migration in hepatocellular carcinoma. (September 2017) - Liu, Xu-Hui; Yang, Yu-Feng; Fang, Heng-Ying; Wang, Xue-Hua; Zhang, Mei-Fang; Wu, Dan-Chun
Highlights: CEP131 is increased in HCC and associated with poor outcomes in two independent cohorts containing 802 patients with HCC. CEP131 promotes cell proliferation and migration via activation of PI3K/AKT signaling pathway. Nucleophosmin interacts with CEP131 to maintain its protein stability. Abstract: Centrosomal proteins have been implicated in the progression of human diseases. CEP131 plays important roles in centrosome duplication and genome stability, but its role in cancers remains largely unknown. Here, we showed that CEP131 expression was increased in hepatocellular carcinoma (HCC), compared to the paracarcinoma tissues, at both mRNA and protein levels. High CEP131 expression was closely associated with tumor size ( P = 0.020), tumor capsule ( P = 0.043), TNM stage ( P = 0.007) and tumor differentiation ( P = 0.019). Furthermore, patients with high expression of CEP131 were accompanied with worse overall and disease-free survivals in our and TCGA cohorts consisting of a total of 802 cases. The prognostic value of CEP131 was further confirmed by stratified survival analysis. Multivariate cox regression model indicated that CEP131 was an independent factor for overall survival (hazard ratio = 1.762, 95% confident interval: 1.443–2.151, P < 0.001). In vitro data demonstrated that nucleophosmin (NPM) physically bound to CEP131 and maintained its protein stability. Overexpression of CEP131 in HCC cell lines enhanced cell proliferation and migration, whereas the knockdown of CEP131 led to the opposite phenotypes. Further studies demonstrated that CEP131 exhibited oncogenic activity via activation of PI3K/AKT signaling pathway. Taken together, our findings suggest CEP131 serves as a potential prognostic biomarker in HCC, and functions as an oncogene in this deadly disease.